Evaluating Effectiveness and Efficiency of the Control (Supervision) Activities - Добролюбова, Елена; Южаков, Владимир (Public Administration Issues, 2015)
For the past 15 years, a number of attempts have been made to optimize public inspections, reduce associated administrative barriers, and limit excessive interference with economic activities of businesses. However, the results achieved have appeared to be below initial expectations since some reforms have not been finished, some solutions have been compromised, and the classical collision of interests between inspectors and subjects of inspections has remained. One of the key reasons for insufficient results from the past initiatives to improve control and inspection activities stems from the lack of attention and variation in the understanding of outcomes and outputs of inspection activities. Lack of such understanding leads to developing performance evaluation systems, which were not always outcome oriented. The article presents a review of inspections performance evaluation practices and various scientific approaches to conducting such evaluations. The key finding of the paper is the need to use a system of performance indicators. Such a system should characterize effectiveness of inspections both in terms of various aspects of control activities (preventing and reducing risk levels, minimizing possible negative effects and repairing the damage done), and with a view to various levels of result (outcomes, intermediate outcomes, outputs). Evaluation of inspections efficiency calls for measuring both government and business administrative costs related to control activities. Implementation of this comprehensive approach would balance the evaluation system and contribute to better orienting inspection bodies’ activities to attain outcomes important to the public.